2018
DOI: 10.1007/s11255-018-1958-y
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of bone fractures in a single-centre cohort of hemodialysis patients: a 2-year follow-up study

Abstract: In a group of hemodialysis patients from one centre, T-score in proximal femur, low vitamin D, low BMI, and high FRAX for major osteoporotic fracture were associated with low-trauma fractures, however, in multi-variate analysis only low BMI remained a significant predictor of fracture risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…In 1426 men and women (mean age 67 y), reduced kidney function was associated with significantly lower TBS and a higher probability of fracture (18% vs. 6%, p = 0.01) and low TBS predicted greater incidence of fragility fractures over 4.7 years, independent of BMD and CRFs [ 110 ]. Lower TBS also corresponds with increasing disease severity [ 111 , 112 ]. In hemodialysis patients (mean age 74 y), TBS and not BMD, was a significant, independent predictor of fracture [ 115 ].…”
Section: Resultsmentioning
confidence: 99%
“…In 1426 men and women (mean age 67 y), reduced kidney function was associated with significantly lower TBS and a higher probability of fracture (18% vs. 6%, p = 0.01) and low TBS predicted greater incidence of fragility fractures over 4.7 years, independent of BMD and CRFs [ 110 ]. Lower TBS also corresponds with increasing disease severity [ 111 , 112 ]. In hemodialysis patients (mean age 74 y), TBS and not BMD, was a significant, independent predictor of fracture [ 115 ].…”
Section: Resultsmentioning
confidence: 99%
“…The majority of patients with fracture had shorter hemodialysis duration (<4 years vs. ≥4 years: 40% vs. 17.8%; P = 0.027) and a history of steroid use (non-user vs. user: 21.7% vs. 63.6%; P = 0.004). Although, the medians of the FRAX® results for MOF and hip fracture were higher in the group with fracture, the difference between two groups did not reach statistical significance (fracture vs. no fracture: 9% (1.2–22) vs. 4.3% [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]; P = 0.066 for MOF and 3.8% (0.1–17) vs. 1.9% (0.1–12); P = 0.102 for hip fracture ( Table 1 ). Comparisons of current laboratory values revealed no differences in serum albumin-corrected calcium, phosphate, ALP, PTH, bicarbonate, and hemoglobin concentrations between the two groups.…”
Section: Resultsmentioning
confidence: 95%
“…It is well established that systemic disorder of mineral and bone metabolism due to CKD, also known as CKD-mineral and bone disorder (CKD-MBD), affects bone strength and quality [ 10 , 11 ]. In previous studies in patients with CKD, advanced age; low bone mineral density (BMD); low body mass index (BMI); narcotic and psychoactive medication use; low 25-hydroxyvitamin D [25(OH)D]; abnormal parathyroid hormone (PTH), phosphorus, calcium, and total alkaline phosphatase (ALP) concentrations; and high Fracture Risk Assessment Tool (FRAX®) for major osteoporotic fracture were associated with low-trauma fracture [ 12 , 13 , 14 , 15 , 16 ]. Long-term dialysis vintage was correlated with hip and vertebral fracture in studies with small sample sizes [ 7 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the author recognizes the importance of other markers such as FRAX and low vitamin D level, he defined that only low bone mineral density can be considered as a predictive factor for low impact fractures. 30 Another study conducted in a population of diabetics showed that, although the bone mineral density in prediabetic and diabetic patients is higher than that found in normoglycemics, the bone quality of bone microarchitecture (TBS) showed no difference. 31 In a cohort also performed in diabetics, the importance of TBS evaluation in this population was reinforced, especially in the evaluation of the proximal femur.…”
Section: Discussionmentioning
confidence: 98%